Network Formation and Heterogeneous Risks - Antonio Cabrales; Piero Gottardi (CESifo GmbH, 2024)
We study a new model to study the effect of contract externalities that arise through shock transmission. We model a financial network where good firms enjoy direct and indirect benefits from linking with one another. Bad risks benefit from having a connection with a good firm, but they are a cost to both direct and indirect connections. In efficient networks the good risks should form large connected components with very few bad risks attached. The equilibrium networks, on the other hand, have many more bad risks attached, they are core-periphery structures, and components are also smaller than the efficient ones. We also study extensions with heterogenous "bad risks," with diversity in the costs to good risk firms of linking with bad risks, and with incomplete information.
Keywords: D85; G21; G32; 330; network formation; financial shocks; financial contagion; core periphery; efficiency and equilibrium